Escreventes técnico judiciários e a construção profissional de sua atuação em um foro de violência doméstica e familiar de São Paulo - Kahwage, Tharuell Lima (2025)
Judicial clerks are a group composed mostly of white women, who take up such positions more frequently than men, according to data from the National Council of Justice. They are responsible for practices essential to the functioning of the justice system, performing administrative and routine activities, such as filing cases, serving the public, and drafting legal documents. Despite the centrality of their role and the functions they perform, studies on this group are still incipient, especially when compared to production around the judiciary, an activity of greater preference and notoriety compared to civil servants, who tend to accumulate activities of less autonomy. Based on this scenario, the objective of this research is to understand how the position of judicial technical clerk is constructed, particularly those who work in a court of domestic and family violence against women in the state of São Paulo. I seek to analyze, through narratives produced by interactions of disputes and cooperation between themselves and other actors, what meanings they elaborate on the activities they perform, as well as how processes of gendering and racialization occur in this dynamic. This is an ethnography recorded through a field diary combined with semi-structured interviews, the data from which were subjected to content analysis. The data obtained reveal that the construction of the position is a dynamic process, shaped by social interactions of dispute and cooperation, as well as by the constant negotiation of the meanings present in their narratives.